Studi Perencanaan Sistem Instalasi Penerangan Jalan pada Jembatan Bentang Panjang di Indonesia (Studi Kasus pada Jembatan Suramadu) - Amirulah, Amirulah (Rekayasa, 2008)
Main topic of this reseach is planning instalation system of road lighting and power supply on long main bridge between islands in Indonesia, with object of interest on Suramadu Bridge. In order to guarantee safety and comfortably for Suramadu Brigde user, design of lighting system has to standart wich recommended by CIE (Commission International on Illumination). This research would like to take sample are: different kind of lamp, armature, and lighting equipment which produced by PT. Philips Indonesia. Final result of this research conclude that road lighting lamp which comfortable on Suramadu Bridge is high pressure lighting orhighpressure sodium (SON) SON-TP type. Beside that,armature which comfor tably used on Suramadu Bridge is Velocity SGP 338 type.According with CIE recommenda tion, installing point pattern of lighting on Suramadu Bridge using Opposite System with lamp capacity 400 W or Opposite and Twin Central System with lamp capacity 250 W. Installing of road lighting is recommeded to use duct cable, because its installingfaster than the others, have small failure risk, and easy on planning, operating, commisioning, and expanding on next time. Electrical distribution lines should use radial type 20 kV middle voltage by using sub feeder (transformer) on right and left side of bridge to suppl y road lighting power on Suramadu Bridge. Manual analysis results voltage drop equal as 0,00991Voltatau 0,05 %.If using ETAP Software, this system results voltage drop equal as 0,011Volt atau 0,05503 %. Finally electrical power suppl y system on Suramadu Bridge have approved with voltage drop requirements according with PLN recommends equal as 5%.